Production of Edible Films from Whey-Chia Seed Combinations with Different Plasticizers: Effects on Physicochemical Properties - Fahrullah, Fahrullah; Bulkaini, Bulkaini; Kisworo, Djoko; Septian, I Gede Nano (CELEBES Agricultural, 2025)
The utilization of natural polymer-based feeding films has emerged as an alternative to plastics and as a solution to the problem of environmental pollution. Concurrently, these films maintain the function of maintaining the shelf life, quality, and safety of food products. The objective of this study was to ascertain the effect of varying proportions of whey-chia seed combinations and types of plasticiser on the physicochemical characteristics of food films. The present study employed a completely randomised factorial design, comprising Factor A: whey-chia seed combination (A1 = 1:0.5; A2 = 1:0.75 and A3 = 1:1) and Factor B: type of plasticizer (B1 = sorbitol and B2 = polyethylene glycol/PEG). The interaction between the whey-chia seed combination and the type of plasticizer did not show a significant effect (P>0.05). However, the whey-chia seed combination itself had a significant impact (P<0.01) on film elongation and tensile strength. The utilisation of sorbitol as a plasticiser resulted in enhanced flexibility of the film, thereby rendering it more appropriate for utilisation in healthy and environmentally friendly food applications. The optimal treatment was determined to be a mixture of whey-chia seeds in a 1:1 ratio with sorbitol plasticizer, yielding an elongation at break of 74.23%, tensile strength of 3.997 MPa, and crude fibre content of 15.67%.